Penerapan Teori Tujuan Pemidanaan dalam Perkara Kekerasan terhadap Perempuan: Studi Putusan Hakim - M. Abdul Kholiq; Ari Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2016)
This study examines: first, the tendencies in the type and weight of crime in the judge's decision in the criminal case of violence against women. Second, the application of the theory of criminal prosecution. This is a normative-legal research with the legal materials that were analyzed using a descriptive-qualitative analysis. From the results of research and discussion conducted, it can be concluded, first: judges always choose to impose the type of imprisonment. The trend for choosing such type was caused by two factors, namely the pattern of criminal threatening in legislation and the nature of crimes of violence against women that substantively is relatively serious. Meanwhile, regarding the weight of sentence imposed, the judge's decisions tend to be various but on average are quite heavy, that is the punishment of 3 (three) to 4 (four) years in jail. Such tendency showed the alignment towards women as the victims of violence crime. The second conclusion showed that the most dominant theories used are the theory of retribution. With the use of this theory it means that judges tend to pay attention to the interests of women as victims.